Influence of principal management, work climate on teacher performance through teacher work motivation - Noorhapizah, Noorhapizah; Suriansyah, Ahmad; Abidin, Muhammad (Trigin Institute, 2023)
This study looked at how primary school teachers in Awayan Subdistrict were affected by the work environment, work motivation, and performance of principal management. The correlation method is used in this quantitative study. The populace was 156 instructors and 112 respondents were taken as the examination test utilizing relative arbitrary inspecting method. A questionnaire instrument was used for data collection, and descriptive analysis, the classical assumption test, multiple linear regression analysis, and path analysis were used for data analysis. The outcomes showed that the variable relapse esteem was a positive number like the relapse coefficient of head the executives execution on educator execution (X1-Y) of 0.583, the relapse coefficient of head the board execution on instructor work inspiration (X1-Z) of 0.533, the relapse coefficient of work environment school on instructor execution (X2-Y) of 0.412, the relapse coefficient of work environment on work inspiration (X2-Z) of 0.659, the relapse coefficient of instructor work inspiration on instructor execution (Z-Y) of 0.532, the relapse coefficient of head the board execution by implication through educator work inspiration on instructor execution (X1-Z-Y) of 0.284 and the relapse coefficient of work environment in a roundabout way through educator work inspiration on instructor execution (X2-Z-Y) of 0.351.